The Role of the Islamic Education Section in Enhancing Student Academic Performance in Yogyakarta - Abshor, Muhammad Ulil; Rahmah, Via (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2024)
Purpose – This study investigates the role of the Islamic Education Section of the Ministry of Religious Affairs in Yogyakarta in improving student academic performance. Design/methods – Employing a qualitative case study approach, data were collected through observations, interviews, and documentation from key informants, main informants, and supporting informants involved with the Islamic Education Section. Findings – The findings reveal that the Section significantly contributes to academic achievements through comprehensive services, guidance, and activities such as Musabaqah Tilawatil Qur’an (MTQ) and the Islamic Education Skills and Arts Week (Pentas PAI). These programs enhance students' interest, talents, and understanding of Islamic principles, fostering balanced development. Research implications/limitations – The study's scope is limited to Yogyakarta, and the primary reliance on qualitative data may limit the generalizability of the findings. Further research could include a broader range of regions and employ mixed-method approaches to validate and expand upon these results. Practical implications – Educational policymakers should consider integrating religious education with mainstream academic curricula to foster holistic student development. The success of the MTQ and Pentas PAI programs underscores the potential of such integrated educational approaches in promoting academic and moral growth. Originality/value – This study highlights the crucial role of religious education in nurturing well-rounded individuals and offers a model that can be adapted and implemented in various educational systems to enhance student outcomes holistically.